Synthesis of mesoporous Ca-MCM catalysts and their use in suitable multicomponent synthesis of polyfunctionalized pyrans - Nope Vargas, Eliana Rocío (2017)
Mesoporous Ca-MCM catalysts were prepared using a mixture of CaCO3, TEOS, cetyl trimethyl ammonium bromide (CTAB), triethanolamine (TEA), ethanol and H₂O. Three catalysts with different CaCO3 contents, M-Ca 1 %, M-Ca 5 % and M-Ca 10 %, respectively, were prepared and characterized by N₂ physisorption, XRD, FT-IR, XPS, TPD-CO₂ and Pyridine-FTIR. A green and simple protocol was developed for the synthesis of 6-amino-4H-pyran scaffolds through a multicomponent coupling reaction of an aldehyde, malononitrile, and 1,3-dicarbonyl compound in different reaction solvents. This procedure was performed at room temperature (20 °C), obtaining good and excellent yields of 4H-pyran derivatives. The mesoporous materials are insoluble in polar media, which allows easy removal of the reaction products without affecting their catalytic activity. The leaching test showed an excellent stability, and Ca-MCM catalysts can be used three times without appreciable loss of their catalytic activity.